PLCζ Induced Ca2+ Oscillations in Mouse Eggs Involve a Positive Feedback Cycle of Ca2+ Induced InsP3 Formation From Cytoplasmic PIP2 - Sanders, Jessica R.; Ashley, Bethany; Moon, Anna; Woolley, Thomas E.; Swann, Karl (Frontiers in Cell and Developmental Biology, 2018)
Egg activation at fertilization in mammalian eggs is caused by a series of transient increases in the cytosolic free Ca2+ concentration, referred to as Ca2+ oscillations. It is widely accepted that these Ca2+ oscillations are initiated by a sperm derived phospholipase C isoform, PLCz that hydrolyses its substrate PIP2 to produce the Ca2+ releasing messenger InsP3. However, it is not clear whether PLCz induced InsP3 formation is periodic or monotonic, and whether the PIP2 source for generating InsP3 from PLCz is in the plasma membrane or the cytoplasm. In this study we have uncaged InsP3 at different points of the Ca2+ oscillation cycle to show that PLCz causes Ca2+ oscillations by a mechanism which requires Ca2+ induced InsP3 formation. In contrast, incubation in Sr2+ media, which also induces Ca2+ oscillations in mouse eggs, sensitizes InsP3-induced Ca2+ release. We also show that the cytosolic level Ca2+ is a key factor in setting the frequency of Ca2+ oscillations since low concentrations of the Ca2+ pump inhibitor, thapsigargin, accelerates the frequency of PLCz –induced Ca2+ oscillations in eggs, even in Ca2+ free media. Given that Ca2+ induced InsP3 formation causes a rapid wave during each Ca2+ rise, we use a mathematical model to show that InsP3 generation, and hence PLCz’s substate PIP2, has to be finely distributed throughout the egg cytoplasm. Evidence for PIP2 distribution in vesicles throughout the egg cytoplasm is provided with a rhodamine-peptide probe, PBP10. The apparent level of PIP2 in such vesicles could be reduced by incubating eggs in the drug propranolol which also reversibly inhibited PLC induced, but not Sr2+ induced, Ca2+ oscillations. These data suggest that the cytosolic Ca2+ level, rather than Ca2+ store content, is a key variable in setting the pace of PLCz induced Ca2+ oscillations in eggs, and they imply that InsP3 oscillates in synchrony with Ca2+ oscillations. Furthermore, they support the hypothesis that PLCz and sperm induced Ca2+ oscillations in eggs requires the hydrolysis of PIP2 from finely spaced cytoplasmic vesicles.